EFL Students’ Perception of DeepL Translation Tool Utilization in Translating Scientific Published Research Articles - Arnita, Ayu; Maulina, Maulina; Rusli, Tri Indah (LPPM Universitas PGRI Semarang, 2025)
Artificial intelligence (AI) technology advancements have given us language learning tools like DeepL, renowned for its translation accuracy and fluency. Students often use DeepL to understand scientific published articles for the purpose of composing thesis paper in the final year of their study. However, research on students' perceptions of the use of DeepL, especially in the translation of scientific articles, is still limited. This study aims to explore the perceptions of tertiary EFL students towards DeepL utilization, particularly in helping them to understand scientific articles in English. This research used a qualitative approach with a case study design. Data were collected through in-depth interviews with final-year students who were selected using a purposive sampling technique. Data analysis was conducted using Braun and Clarke's (2006) thematic analysis method. The results showed that students have positive perceptions of DeepL because of its ability to translate complex academic terms, provide accurate and contextual translations, and accelerate understanding of academic literature. In addition, students consider DeepL is easy to use, accessible on various devices, and rarely experience technical problems. Most students plan to continue using DeepL in their academic studies and recommend it to their peers. This finding confirms that DeepL has an important role as a translation tool in supporting students' understanding of English scientific articles in thesis writing.